Preterm Preeclampsia and Timing of Delivery: A Systematic Literature Review - Guida, José Paulo de Siqueira; Surita, Fernanda Garanhani; Parpinelli, Mary Angela; Costa, Maria Laura (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Introduction Preeclampsia, a multifactorial disease with pathophysiology not yet fully understood, is a major cause of maternal and perinatal morbidity and mortality, especially when preterm. The diagnosis is performed when there is an association between arterial hypertension and proteinuria or evidence of severity. There are unanswered questions in the literature considering the timing of delivery once preterm preeclampsia has been diagnosed, given the risk of developing maternal complications versus the risk of adverse perinatal outcomes associated with prematurity. The objective of this systematic review is to determine the best timing of delivery for women diagnosed with preeclampsia before 37 weeks of gestation.Methods Systematic literature review, performed in the PubMed database, using the terms preeclampsia, parturition and timing of delivery to look for studies conducted between 2014 and 2017. Studies that compared the maternal and perinatal outcomes of women who underwent immediate delivery or delayed delivery, in the absence of evidence of severe preeclampsia, were selected.Results A total of 629 studies were initially retrieved. After reading the titles, 78 were selected, and their abstracts, evaluated; 16 were then evaluated in full and, in the end, 6 studies (2 randomized clinical trials and 4 observational studies) met the inclusion criteria. The results were presented according to gestational age range (< 34 weeks and between 34 and 37 weeks) and by maternal and perinatal outcomes, according to the timing of delivery, considering immediate delivery or expectant management. Before 34 weeks, the maternal outcomes were similar, but the perinatal outcomes were significantly worse when immediate delivery occurred. Between 34 and 37 weeks, the progression to severe maternal disease was slightly higher among women undergoing expectant management, however, with better perinatal outcomes.Conclusions When there is no evidence of severe preeclampsia or impaired fetal well-being, especially before 34 weeks, the pregnancy should be carefully surveilled, and the delivery, postponed, aiming at improving the perinatal outcomes. Between 34 and 37 weeks, the decision on the timing of delivery should be shared with the pregnant woman and her family, after providing information regarding the risks of adverse outcomes associated with preeclampsia and prematurity.
Keywords: preeclampsia; delivery; prematurity; preterm preeclampsia